EKSPLORASI ETHNOMATEMATIKA BUSANA KESULTANAN KERATON KADRIAH PONTIANAK - Indrawati, Nur; Komalasari (Al-'Adad: Jurnal Tadris Matematika, 2025)
Education and culture are two interrelated entities. Mathematics is an abstract field of study, making it difficult for students to understand its concepts. Culture plays a role in providing concrete objects for learning mathematics. The integration of culture into mathematics is known as ethnomathematics. This study aims to explore the ethnomathematical elements in the attire of the Pontianak Sultanate and relate them to geometric concepts in mathematics education. This research is qualitative with an ethnographic approach. Data were collected through interviews, observations, and documentation, with Syech Arsula as the main informant. The findings indicate that various geometric elements, such as symmetry, patterns, and basic shapes, are present in the design of the Pontianak Sultanate attire. These findings can serve as a learning resource for geometry education in schools.